2011
DOI: 10.1093/nar/gkr1234
|View full text |Cite
|
Sign up to set email alerts
|

Concerted nicking of donor and chromosomal acceptor DNA promotes homology-directed gene targeting in human cells

Abstract: The exchange of genetic information between donor and acceptor DNA molecules by homologous recombination (HR) depends on the cleavage of phosphodiester bonds. Although double-stranded and single-stranded DNA breaks (SSBs) have both been invoked as triggers of HR, until very recently the focus has been primarily on the former type of DNA lesions mainly due to the paucity of SSB-based recombination models. Here, to investigate the role of nicked DNA molecules as HR-initiating substrates in human somatic cells, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…We too used an EGFP-based reporter system with a short homologous region (795 bp; rNCO assay) and observed low efficiencies of targeted knockin by tandem paired nicking compared with those obtained by the Cas9-nuclease-based method. Several previous studies have described the enhancement of targeted knockin by creating two nicks, one on the donor and the other within the genome, at different positions (Chen et al, 2017;Davis and Maizels, 2014;Gonç alves et al, 2012;Nakajima et al, 2018). This strategy, however, requires careful donor design, including the incorporation of a foreign sequence or silent mutation into the donor, which are eventually integrated into the genome upon targeted knockin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We too used an EGFP-based reporter system with a short homologous region (795 bp; rNCO assay) and observed low efficiencies of targeted knockin by tandem paired nicking compared with those obtained by the Cas9-nuclease-based method. Several previous studies have described the enhancement of targeted knockin by creating two nicks, one on the donor and the other within the genome, at different positions (Chen et al, 2017;Davis and Maizels, 2014;Gonç alves et al, 2012;Nakajima et al, 2018). This strategy, however, requires careful donor design, including the incorporation of a foreign sequence or silent mutation into the donor, which are eventually integrated into the genome upon targeted knockin.…”
Section: Discussionmentioning
confidence: 99%
“…Although single nicks have been found to trigger HDR with efficiency generally lower than that triggered by DSBs (Bolukbasi et al, 2016;Cornu et al, 2017;Komor et al, 2017), further studies have shown that the efficiency of HDR can be improved by the use of two nickases so that they create no DSB in the genome. The majority of these studies created one nick on the donor DNA and the other within the genome, at different positions, by using two nickases (Chen et al, 2017;Davis and Maizels, 2014;Gonç alves et al, 2012;Nakajima et al, 2018). In this study, we explored a distinct and less-well-described strategy of using Cas9 nickases for targeted knockin, which is called ''tandem paired nicking'' (Chen et al, 2017) or ''tandem nicking'' (Nakajima et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Concerted nicking of both donor and target DNA has been reported to stimulate HDR (30). This raises the possibility that the prevalence of nicks in the genome may stimulate HDR not only between sister chromatids, which would not alter genomic sequence, but also between homologous chromosomes, which could result in loss of heterozygosity, a common form of genomic instability in tumor cells.…”
Section: Nicked Dsdna Donors Promote Efficient Alternative Hdr At a Nmentioning
confidence: 99%
“…We too employed an EGFP-based reporter system with a short homologous region (795 bp; rNCO assay) and observed low efficiencies of targeted knock-in via tandem paired nicking compared with those obtained by the Cas9 nuclease-based method. Several previous studies have described enhancement of targeted knock-in by creating two nicks, one on the donor and the other within the genome, at different positions (Chen et al, 2017;Davis and -12 -Maizels, 2014;Goncalves et al, 2012;Nakajima et al, 2018). This strategy, however, requires careful donor design, including the incorporation of a foreign sequence or silent mutation into the donor, which are eventually integrated into the genome upon targeted knock-in.…”
Section: Discussionmentioning
confidence: 99%
“…Although single nicks have been found to trigger HDR with efficiency generally lower than that triggered by DSBs (Bolukbasi et al, 2016;Cornu et al, 2017;Komor et al, 2017), further studies have -4 -shown that the efficiency of HDR can be improved by the use of two nickases so that they create no DSB in the genome. The majority of these studies created one nick on the donor DNA and the other within the genome, at different positions, using two nickases (Chen et al, 2017;Davis and Maizels, 2014;Goncalves et al, 2012;Nakajima et al, 2018). In this study, we explored a distinct and less well described strategy of using Cas9 nickases for targeted knock-in, which is called 'tandem paired nicking' (Chen et al, 2017), or 'tandem nicking' (Nakajima et al, 2018).…”
Section: Introductionmentioning
confidence: 99%